Explaining Broadband Adoption in Rural Australia: Modes of Reflexivity and the Morphogenetic Approach1 - Dobson, Philip; Jackson, Paul; Gengatharen, Denise (MIS Quarterly, 2013)
Universal fast broadband is currently being implemented by the Australian government. It is the largest single project in Australia’s history. Represented as a nation-building exercise by the government and many public and private promoters, it is vilified by others as a massive waste of taxpayers’ money. Ultimately the target of successful universal availability will require that metropolitan installations subsidize rural adoption. The take-up of these facilities, particularly in regional and remote areas, constitutes a complex, multi-factorial scenario in which political, personal, and organizational decisions are shaped by physical, cultural, economic, and ideological elements. Critical realism is proposed here as an aid for examining the complex reality of rural adoption for communities and small businesses in the regions. This article highlights the importance of considering individual reflexivity in explaining the adoption decision and potential adoption barriers.